Antibiotic strategies for eradicating Pseudomonas aeruginosa in people with cystic fibrosis - Langton Hewer, Simon C.; Smyth, Alan R. (Wiley, 2014)
Background: Respiratory tract infection with Pseudomonas aeruginosa occurs inmost people with cystic fibrosis. Once chronic infection is established, Pseudomonas aeruginosa is virtually impossible to eradicate and is associated with increased mortality and morbidity. Early infection may be easier to eradicate. This is an update of a Cochrane review first published in 2003, and previously updated in 2006 and 2009. Objectives: To determine whether antibiotic treatment of early Pseudomonas aeruginosa infection in children and adults with cystic fibrosis eradicates the organism, delays the onset of chronic infection, and results in clinical improvement. To evaluate whether there is evidence that a particular antibiotic strategy is superior to or more cost-effective than other strategies and to compare the adverse effects of different antibiotic strategies (including respiratory infection with other micro-organisms). Search methods: We searched the Cochrane Cystic Fibrosis and Genetic Disorders Group Trials Register comprising references identified from comprehensive electronic database searches and handsearches of relevant journals and abstract books of conference proceedings. Most recent search: 08 September 2014. Selection criteria: We included randomised controlled trials of people with cystic fibrosis, in whom Pseudomonas aeruginosa had recently been isolated from respiratory secretions. We compared combinations of inhaled, oral or intravenous antibiotics with placebo, usual treatment or other combinations of inhaled, oral or intravenous antibiotics. We excluded non-randomised trials, cross-over trials, and those utilising historical controls. Data collection and analysis: Both authors independently selected trials, assessed risk of bias and extracted data. Main results: The search identified 49 trials; seven trials (744 participants) with a duration between 28 days and 27 months were eligible for inclusion. Three of the trials are over 10 years old and their results may be less applicable today given the changes in standard treatment. Some of the trials had low numbers of participants and most had relatively short follow-up periods; however, there was generally a low risk of bias from missing data. In most trials it was difficult to blind participants and clinicians to treatment given the interventions and comparators used. Two trials were supported by the manufacturers of the antibiotic used. Evidence from two trials (38 participants) at the two-month time-point showed treatment of early Pseudomonas aeruginosa infection with inhaled tobramycin results in microbiological eradication of the organism from respiratory secretions more often than placebo, odds ratio 0.15 (95% confidence interval 0.03 to 0.65) and data from one of these trials, with longer follow up, suggested that this effect may persist for up to 12 months. One randomised controlled trial (26 participants) compared oral ciprofloxacin and nebulised colistin versus usual treatment. Results after two years suggested treatment of early infection results in microbiological eradication of Pseudomonas aeruginosa more often than no anti-pseudomonal treatment, odds ratio 0.12 (95% confidence interval 0.02 to 0.79). One trial comparing 28 days to 56 days treatment with nebulised tobramycin solution for inhalation in 88 participants showed that both treatments were effective and well-tolerated, with no notable additional improvement with longer over shorter duration of therapy. However, this trial was not powered to detect non- inferiority or equivalence. A trial of oral ciprofloxacin with inhaled colistin versus nebulised tobramycin solution for inhalation alone (223 participants) failed to show a difference between the two strategies, although it was underpowered to show this. A further trial of inhaled colistin with oral ciprofloxacin versus nebulised tobramycin solution for inhalation with oral ciprofloxacin also showed no superiority of the former, with increased isolation of Stenotrophomonas maltophilia in both groups. A recent, large trial in 306 children aged between one and 12 years compared cycled nebulised tobramycin solution for inhalation to culture-based therapy and also ciprofloxacin to placebo. The primary analysis showed no difference in time to pulmonary exacerbation or proportion of Pseudomonas aeruginosa positive cultures. An analysis performed in this review (not adjusted for age) showed fewer participants in the cycled therapy group with one or more isolates of Pseudomonas aeruginosa, odds ratio 0.51 (95% CI 0.31 to 0.28). Authors’ conclusions: We found that nebulised antibiotics, alone or in combination with oral antibiotics, were better than no treatment for early infection with Pseudomonas aeruginosa. Eradication may be sustained for up to two years. There is insufficient evidence to determine whether antibiotic strategies for the eradication of early Pseudomonas aeruginosa decrease mortality or morbidity, improve quality of life, or are associated with adverse effects compared to placebo or standard treatment. Four trials of two active treatments have failed to show differences in rates of eradication of Pseudomonas aeruginosa. There have been no published randomised controlled trials that investigate the efficacy of intravenous antibiotics to eradicate Pseudomonas aeruginosa in cystic fibrosis. Overall, there is still insufficient evidence from this review to state which antibiotic strategy should be used for the eradication of early Pseudomonas aeruginosa infection in cystic fibrosis.